Structural geology and personal computers - De Paor, Declan G. (Computer methods in the geosciences, 1996)
This book will help structural geologists keep abreast of rapid changes in work practices resulting from the personal computer revolution. It is organized into six parts: I Computer-Aided Learning; II Microstructural Analysis; III Analysis of Orientation Data; IV Strain and Kinematic Analysis; V Mathematical and Physical Modeling; VI Structural Mapping and GIS. The 45 contributing authors explain how to: set up computer-aided teaching and learning facilities on a low budget; illustrate tectonic strain concepts with a drawing program; integrate multimedia presentations into structural coursework; analyze microstructures with computer-aided microscopy; produce sophisticated stereonets with custom software for both the Mac and IBM PC; evaluate orientation data using a spreadsheet program; model the development of macrostructures and microstructures numerically; integrate structural and geophysical data; and apply PC technology to the production of structural maps, cross sections, and block diagrams. The editor's own contributions reveal the inner workings of his renowned structural research applications which are used in hundreds of universities worldwide. Commercial and non-commercial applications of particular interest to structural geologists are reviewed. This volume will prove an invaluable resource for professors, instructors, and research students, as well as research scientists in the public services and exploration industries. If you are such a person, have you lectured with the aid of a gyroscopic mouse? Or used Bzier curves to model heterogeneous deformation? Or analyzed a fold structure using a digital terrain model? If not, you'll need to rush out and buy this book before the next wave of new technology hits!